Factors Influencing Customer Interest in Using Financing Products at Bank KB Bukopin Syariah Yogyakarta - Pipit Puspita; Rintan Nuzul Ainy (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
Islamic banking is one of the targets in the economic sector that will be developed and focused on in Indonesia. The advantage possessed by Islamic banking is that it lies in an operational system based on Sharia principles. However, behind these advantages, there are some people who do not understand related to regulations and sharia principles so this can trigger the emergence of negative perceptions which are a factor in reducing customer interest in using sharia bank products, especially financing products. This study aims to examine the effect of knowledge of financing products, perceived service quality, perceived product quality, and perceived profit-sharing ratios on customers’ interest in using financing products at Bank KB Bukopin Syariah Yogyakarta. This research is quantitative research. The data source is using primary data. The sample selection used a purposive sampling technique. The analytical method uses multiple linear regression assisted by SPSS version 29 software. The results of this study indicate that the variable knowledge of financing products has a significant influence on customers’ interest in using financing products at Bank KB Bukopin Syariah Yogyakarta. Meanwhile, perceptions of service quality, perceptions of product quality, and perceptions of profit-sharing ratios do not have a significant effect on customers’ interest in using financing products at Bank KB Bukopin Syariah Yogyakarta. This study recommends the need factor to determine the influence of customer interest in using financing products in Islamic banks.